Institutionalization of the Metaverse Based on the Development of the Exabyte Economy and Gig Economy - Kateryna Kraus; Nataliia Kraus (Journal of Vasyl Stefanyk Precarpathian National University, 2025)
The development of the Metaverse will depend on the rapid development of the exabyte economy and a new technical and technological impetus to improve the tools for the functioning of the gig economy. The article substantiates the existing products, services and national projects of the Metaverse in the context of the accelerated formation of the exabyte economy. It is noted that the exabyte economy, by improving its throughput, lays an innovative and digital basis for the development of the Metaverse ecosystem and the optimization of business processes through the digitalization of business models of entrepreneurship. The connection of the Metaverse with the exabyte economy and the gig economy is analyzed through the prism of digitalization and breakthrough innovations. The article reveals that the technologies that are actively developing the exabyte economy are AI, IoT, Big Data, and blockchain technology. The structural components of the Metaverse engineering in the context of the digital transformation of the global world-system are presented. It’s indicated that the institutional, technical and technological components and the crypto ecosystem are key drivers of the progressive development of the Metaverse using virtual, augmented and augmented reality, the application of smart contracts, and patentability for virtual goods. It’s noted that a global, institutionalized, interacting network of 3D virtual worlds is demonstrated in real time. An attempt has been made to reveal the characteristic features, types, and models of the Metaverse in the conditions of the development of the gig economy, including the currently existing ones: 2 types of Metaverses; 3 models of ownership of the Metaverse. The goods produced by digitized businesses in physical space have every chance of becoming tools for the progressive development of the virtual environment of the Metaverse. Scientists are of the opinion that it was the technological wave of the last 5 years that gave rise to a number of breakthrough innovations and high technologies, which allowed forming the basis of the exabyte economy and the gig economy.